Prostate bed irradiation with alternative radio-oncological approaches (PAROS): a prospective, multicenter and randomized phase III trial - Körber, Stefan A.; Katayama, Sonja; Sander, Anja; Jäkel, Cornelia; Häfner, Matthias; Debus, Jürgen; Herfarth, Klaus (Radiation oncology, 2019)
For patients with treatment-naïve carcinoma of the prostate, hypofractionated irradiation becomes more and more popular. Due to the low α/β value of prostate cancer, increased single dose leading to a shortened treatment period seems to be safe and feasible. However, reliable data is lacking for post-prostatectomy patients so far. Further, the role of proton therapy is still under debate. Two prospective phase II trials with both, hypofractionated photon and proton therapy, provided promising results.